Techno-economic-enviro optimization analysis of diesel/PV/wind with pumped hydro storage for Mentawai Island microgrid - Syafii Syafii; Wati Wati; Rahmad Fahreza (Institute of Advanced Engineering and Science, 2021)
This paper presents a techno-economic analysis and environment assessment of hybrid photovoltaic (PV), wind turbine (WT), and diesel genset (DG) with pumped hydro storage (PHS) for a rural microgrid system. The analysis is carried out for a case study with Mentawai community load demand of 165.44 kWh/day at a peak load of 20.46 kW. The Homer simulation results show that there are eight feasible configurations, which the optimal hybrid system configuration to supply community load is the configuration with PV/DG/PHS. An optimal system has been achieved for the lowest NPC of Indonesian rupiah (IDR) 3,00 B consist of 15 kWp PV modules, 1 unit of PHS and a solar inverter with a size 25 kW. The net present cost and payback period are in accordance with criteria for the economic feasibility analysis method of a project. However, the cost of energy is greater than the electrical utility tariff, but this value can be considered for applications in the remote island area. Therefore, the project still feasible to be implemented. Since the renewable fraction of the system is increased hence this proposed system will have the lowest carbon emission.